Compression of fluid-filled polymeric capsules and inverse analysis to determine nonlinear viscoelastic properties. (1st June 2015) - Nguyen, Nhung; Wineman, Alan; Waas, Anthony
Abstract: Experimental results obtained by compressing fluid-filled polymeric capsules between two flat, parallel plates, are analyzed to obtain information on the capsule wall material properties. Reaction force–displacement–time response of the capsule and the contact area during the compression process are recorded and fitted by an inverse analysis. This inverse analysis is a surrogate model based on a Kriging estimator. It is built upon optimizing the error between simulated force–time responses from a finite element (FE) model of the experiment with the corresponding experimental data. In addition, the contact area information during the compression test is also used to give more insight into the modeling of the problem. Since the capsule is subjected to large relative displacements of the top plate, material and geometric non-linearity are incorporated in the FE model. As observed from experiments, the capsule material exhibits time-dependent characteristics. Therefore, in this study, a nonlinear viscoelastic (NLV) constitutive relation for modeling the capsule shell material is employed. The enclosed fluid is assumed to be incompressible and in a steady state. Combining the FE model and the Kriging estimator allowed for an automatic identification of the NLV properties of capsule walls from a general 3D compression test. The study can be extended to the characterization of the nonlinear viscoelastic characteristics of biological cells which might be applicable for the purpose of establishing biomarkers.